A Scottish Government consultation on implementation of the Gender Representation on Public Boards (Scotland) Act 2018 : (1) Regulations setting out reporting arrangements, (2) Statutory guidance on the operation of the Act.: (1) Regulations setting out reporting arrangements, (2) Statutory guidance on the operation of the Act. (2019) - Unknown
No abstract available